UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL AKAR BAJAKAH TAMPALA (Spatholobus Littoralis Hassk) MENGGUNAKAN METODE PEREDAMAN RADIKAL BEBAS DPPH - Sari, Wina Astri; Tahir, Masdiana; Baits, Muzakkir (PHARMACY UMI JOURNAL SYSTEM, 2024)
Bajakah tampala (Spatholobus littoralis Hassk.) is a plant that lives on vines in tropical areas. This plant comes from Sebuku Village, North Kalimantan. The Bajakah Tampala plant contains saponins, flavonoids and tannins. The roots of the Bajakah Tampala plant are thought to have strong antioxidant activity which is able to reduce the activity of free radicals. The aim of this research is to analyze the antioxidant activity of Bajakah Tampala roots using the DPPH reduction method using a UV Vis spectrophotometer which is based on calculating the IC50 value. The results of this study indicate that the ethanol extract of Bajakah Tampala roots has antioxidant activity against DPPH free radicals with an IC50 value of 9.206 µg/mL. which is included in the group of very strong antioxidants.